Elastic Linear Analysis of Connecting Rods for Single Cylinder Four Stroke Petrol Engines Using Finite Element Method - Didin Zakariya Lubis; Andoko Andoko (Journal of Mechanical Engineering Science and Technology (JMEST), 2019)
A connecting rod is one of the most critical parts in engine assembly which transfers energy from the piston to the crankshaft. The connecting rod mainly undergoes tensile and compressive loading under engine cyclic process. The forces acting on the connecting rod are forces due to maximum combustion pressure and forces due to the inertia of the connecting rod. This research aimed to analyze the design of the connecting rod of single-cylinder four-stroke engines. This study used CAD software for modeling and structural design. Stresses generated across all the locations of the connecting rod were evaluated using FEA Software. Elastic linear analysis of model design was also performed. The simulation results in this study have led to the conclusion that failure occurred due to the incorrect selection of materials. Among all materials under study, AA 6061 is considered the most suitable material for use at high RPM. In fact, aluminum is preferable for use at high RPM.